Resolution of a titanium implant fracture after a recurrent trauma - Cardoso, Leandro de Carvalho [UNESP]; Luvizuto, Eloa Rodrigues [UNESP]; Trevisan, Carolina Lunardelli [UNESP]; Garcia, Idelmo Rangel [UNESP]; Barioni, Sônia Regina Panzarini [UNESP]; Poi, Wilson Roberto [UNESP] (Wiley-Blackwell Publishing, Inc, 2010)
Post-traumatic complications occasionally lead to tooth loss as well as the need for future implants. However, rehabilitation with endosseous osseointegrated implants does not protect the patient from the risk of suffering a new trauma. Implant fracture and the damage of the hexagon are post-traumatic complications that guide the clinician to preparing a more intricate treatment plan. The authors present a clinical case of a recurrent trauma of maxillary implant fracture. The treatment plan was to remove the implants followed by autogenous bone grafting to correct the defect. Two titanium implants were replaced, followed by connective tissue graft after allowing complete the healing process of the bone graft to occur. In the postoperative period of 6 months, satisfactory results have been shown as regards soft and hard tissues wound healing.